2022
DOI: 10.1155/2022/8274445
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship between Parenting Style and Career Planning of Vocational Students by Educational Psychology under Information Technology

Abstract: It is aimed at studying the role of parenting style on the career planning of vocational students in the context of information technology. This design takes the first-year and second-year students of two higher vocational colleges as the survey objects. From the perspective of educational psychology, firstly, the parenting style scale of these students is constructed, and meanwhile, the dimension design of career planning is carried out. Secondly, through the questionnaire survey, the career planning of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…At the same time, the established and refined career development goals on the contrary guide students to more clearly carry out professional skills learning, institutional activities involved in them and community practice activities involved in them in the study of career competencies carefully prepared. Career planning culture education guides students in the direction of personal development in the macroeconomy, and in the specific knowledge and technical professional learning, and better preparation for professional knowledge learning and practice in advance in turn enhances students' identity and courage [5,6]. The cultural education of career development planning and advance preparation of personal career ability produce two-way interaction, and finally assist college students to establish and perfect their career ability [7].…”
Section: Help Students Build and Improve Their Career Abilitiesmentioning
confidence: 99%
“…At the same time, the established and refined career development goals on the contrary guide students to more clearly carry out professional skills learning, institutional activities involved in them and community practice activities involved in them in the study of career competencies carefully prepared. Career planning culture education guides students in the direction of personal development in the macroeconomy, and in the specific knowledge and technical professional learning, and better preparation for professional knowledge learning and practice in advance in turn enhances students' identity and courage [5,6]. The cultural education of career development planning and advance preparation of personal career ability produce two-way interaction, and finally assist college students to establish and perfect their career ability [7].…”
Section: Help Students Build and Improve Their Career Abilitiesmentioning
confidence: 99%
“…El control conductual ejerce efectos protectores contra el uso problemático de Internet, aunque estudios más relevantes se basan en una medición simplista de la crianza (Lukavska et al, 2020). La autonomía psicológica está memorablemente asociada con el dominio de la exploración (Dámaso- Flores & Serpa-Barrientos, 2022;Zhang, 2022). Conducta antisocial se refiere a perturbaciones clínicas, conformadas por comportamientos diversos, que perturban el desenvolvimiento normal de los sujetos, con efectos negativos en los individuos y entornos en los que interactúan (González Martínez, 2012).…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%